2021
DOI: 10.1002/ejoc.202101273
|View full text |Cite
|
Sign up to set email alerts
|

PAHs Containing both Heptagon and Pentagon: Corannulene Extension by [5+2] Annulation

Abstract: In memory of Professor Klaus HafnerUtilizing Pd-catalyzed [5 + 2] annulation a series of heptagonextended corannulenes could be synthesized from a borinic acid precursor furnished by CÀ H borylation strategy. Singlecrystal X-ray analysis revealed the presence of two conformational enantiomers crystallizing in a racemic mixture. Through their embedded five-and seven-membered rings these polycyclic aromatic hydrocarbons (PAHs) exhibit both negative and positive curvature and UV/Vis/NIR absorption spectroscopy as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Three-coordinate NHC-borenium cations are strongly electrophilic boron compounds that can be generated from the air- and moisture-stable NHC-boranes and a strong acid. Würthner et al recently developed a synthesis of cyclic borinic acids relying on this chemistry study ( Scheme 29 ); the NHC-borenium species is first generated from 1,3-diisopropylimidazol-2-ylidene borane 91 and HNTf 2 [ 67 , 68 , 69 , 70 ]. The subsequent addition of 92 , led to the cyclic NHC-borane intermediate 93 .…”
Section: Formation Of Two Carbon–boron Bondsmentioning
confidence: 99%
“…Three-coordinate NHC-borenium cations are strongly electrophilic boron compounds that can be generated from the air- and moisture-stable NHC-boranes and a strong acid. Würthner et al recently developed a synthesis of cyclic borinic acids relying on this chemistry study ( Scheme 29 ); the NHC-borenium species is first generated from 1,3-diisopropylimidazol-2-ylidene borane 91 and HNTf 2 [ 67 , 68 , 69 , 70 ]. The subsequent addition of 92 , led to the cyclic NHC-borane intermediate 93 .…”
Section: Formation Of Two Carbon–boron Bondsmentioning
confidence: 99%
“…35 Würthner et al established an elegant synthetic protocol for preparing saddle-shaped corannulene derivatives bearing both a positive and negative curvature at the corannulene and annulated sevenmembered ring moieties. 36 Nevertheless, regardless of these astonishing advances on the preparative synthesis and characterization of azulene derivatives, gas-phase molecular mass growth processes to azulenethe simplest representative of a bicyclic, 10p aromatic molecule formally accessed through fusion of cyclopentadiene and cycloheptatriene ringsalong with its derivatives in high-temperature combustion systems and extraterrestrial settings have not been reported yet, but are fundamental to unravel the gas phase preparation of carbonaceous nanostructures such as curved nanographenes 37,38 and nanoribbons. 39 Here, we provide persuasive testimony on the rst gas phase preparation of the azulene molecule (C 10 H 8 ) along with its naphthalene isomer (C 10 H 8 ) initiated through the reaction of two resonantly stabilized free radicalsfulvenallenyl ðC 7 H 5 Þ…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has reported a method for the construction of heptagon‐embedded PAHs by palladium‐catalyzed [5+2] annulation of cyclic borinic acids with aryl halides (Scheme 1 top left) [16] . Since then we have used this strategy to synthesize PAHs with two embedded azulene units, [17] as well as PAHs with both negative and positive curvature [18] . We conjectured that by using 1‐boraphenalenes as the borinic acid precursor for this synthetic method a series of pleiadiene derivatives could be synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Since then we have used this strategy to synthesize PAHs with two embedded azulene units, [17] as well as PAHs with both negative and positive curvature. [18] We conjectured that by using 1boraphenalenes as the borinic acid precursor for this synthetic method a series of pleiadiene derivatives could be synthesized. Herein, we present the synthesis of a series of π-extended pleiadienes (1 and 2) and benzo [1,2-i:4,5-i']dipleiadienes (BDPs, 3 and 4) and investigate their aromaticity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation